Os gradis e ornamentos de ferro do Colégio Gentil Bittencourt: relação entre a comunidade estudantil, patrimônio e educação museal - FRAIHA, Suzete Montalvão (2019)
The present work has as object of research the iron grids and ornaments of the School Gentil Bittencourt, that during the construction of the building were imported in the great majority to compose the architectonic set as structural and ornamental elements of the building. This study aims to understand the fact that the museum establishes a relationship between patrimony, space and the student community, to investigate the student community's understanding of patrimony, to suggest strategies for educational actions through museum education, from the creation of a museological circuit of knowledge of the object of this study to become known and awaken feeling of belonging and preservation of heritage. During the stages of this research are presented the historical studies about the College and the iron grids and the study of public. It was created a script of knowledge of the expository points of each cultural object with technical description of the material and elaboration of an illustrative folder as a mediation grant. The educational museological actions proposed in this study are the processes used for the knowledge and valuation of the cultural object as historical and museological potential.